2001
DOI: 10.1007/s004170000224
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological correlation in exudative age-related macular degeneration: recurrent choroidal neovascularization

Abstract: A subretinal fibrovascular membrane corresponded with the classic recurrent choroidal neovascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Indeed, this phenomenon of macular neovessel recurrence is frequently observed after CNVM treatment modalities. 85,86 We conclude that the quantitatively distinct features of the EL may help to explain the enhanced susceptibility of the macula to degeneration in AMD and other diseases characterized by neovascularization in the macular region.…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, this phenomenon of macular neovessel recurrence is frequently observed after CNVM treatment modalities. 85,86 We conclude that the quantitatively distinct features of the EL may help to explain the enhanced susceptibility of the macula to degeneration in AMD and other diseases characterized by neovascularization in the macular region.…”
Section: Discussionmentioning
confidence: 87%
“…Typischerweise ist eine subretinale CNV von einem fibrinhaltigen Rand umgeben [1,12]. Die Membran vergrößert sich in ihren Randbereichen durch Aussprossung von Gefäßen in die fibrinö-se Matrix.…”
Section: » Neuerdings Wird Die Injektion Von Anti-vegf Gleichzeitig Munclassified
“…Several authors have studied the pathology of exudative AMD [6,7,8,9,10,11,13,14,15,16,17,18,23,24,25,26,27,28,29,31,32,33,36,37,38,40,42]. Some authors have reported the pathology of massive intraocular hemorrhage complicating age-related macular degeneration in enucleated eyes [10,31].…”
Section: Introductionmentioning
confidence: 99%
“…A series of surgically extracted specimens in hemorrhagic AMD have been studied for the Submacular Surgery Trial, but no separate analysis of these specimens is available [18]. More recently, the histopathological appearance in AMD has been correlated with angiographic characteristics [6,7,23,24,25,26,27,28,29,36,40,42]. In this study the pathologic characteristics of a relatively large series of hemorrhagic maculopathy surgical specimens is reported and compared with those of classic, mixed and occult CNV.…”
Section: Introductionmentioning
confidence: 99%